Friday

April 18, 2014

April 18, 2014

Posted by **kim** on Sunday, April 19, 2009 at 6:52pm.

- math -
**Reiny**, Sunday, April 19, 2009 at 7:23pmcot 2x = 1/tan 2x

= 1/[2tanx/(1-tan^2(x))]

= (1-tan^2(x))/2tanx

= [1 - 1/cot^2(x))/(2/cotx)

= [(cot^2(x) - 1)/cot^2(x)]/[2/cotx]

= (cot^2(x) - 1)/(2cotx)

I don't know if that is the simplest way, I just sort of followed by nose.

you can try sec 2x by noting

sec 2x = 1/cos 2c

then using cos2x = 2cos^2(x) - 1

follow the above procedure.

**Related Questions**

math - when you are determining a formula for cot(2x) using only tan(x) would ...

trig - For each expression in column I, choose the expression from column II to ...

Math - Trigonometry - Verify the following: 1. cos x/(1-sinx)= sec x + tan x 2...

math - how would you create an equation for sec(2x) using only sec(x) and csc(x...

Math-Trig - 1. Create an algebraic expression for sin(arccosx-arcsin3x) 2. The ...

trigonometry repost - Reduce (csc^2 x - sec^2 X) to an expression containing ...

trig - simplify (1-cot^2x sec^2x) / ( cot^2x)

trig - simplify (1-cot^2x sec^2x) / ( cot^2x)

math - Simplify sin^2x+cos^2x+sec^2x -tan^2x+csc^2x-cot^2x

MATH - Determine a formula for sec(2è) using both sec(è) and csc(è). Determine a...